Model of the Teenage Sports Game Gateball Beginner's Guide to the Gateball Sport Game Model - Ramadan, Ramadan; Br Tarigan, Gita Nurgaya; nurras, Raihan; Br Tarigan, Irene Viazza; Barus, Dodi Sahputra; Tarigan, Arif Peristan; Rambe, Arsyad Parlindungan; Nasution, Khoirul Basri (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives. This study seeks to create a model for a gateball sports game tailored for beginners, serving as a tool for enhancing accuracy, compactness, and teamwork. Materials and Methods. The data collection took place in September 2024 at the STOK Bina Guna gateball field, located at Jln. Aluminium Raya No. 77, Tanjung Mulia, Medan. The approach employed in this study follows the Research & Development (R&D) framework from ADDIE, which consists of five stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The population utilized in this study consists of child teenagers, totaling 12 students as subjects for the test trial (practice field). Results The validation employed in the study involves expert justification testing, wherein the tested model is subsequently consulted and evaluated by experts based on the relevant variables. Test attempt conducted during three meetings utilizing ten modified game models in gateball sports for beginner teenagers, aimed at analysis through the completion of a justification questionnaire by expert lecturers (expert judgment). Following validation by expert lecturers, a total of 10 game models were identified as feasible and subsequently subjected to testing. Simulation game This can later serve as a reference for teachers and students to enhance practice in accuracy, compactness, and teamwork. Conclusion. The conclusion represents the final outcome derived from the study. This document presents 10 motion models for sport gate ball, designed for beginners. These models can be effectively utilized as a learning medium and for training through game modifications. It is advisable to conduct further studies, including testing with a larger population, and to assess the long-term impact of game model implementation. This aims to enhance skills, facilitate participation in gate ball, and foster social and emotional development.